Tracking in Caves: Experience Based Reading of Pleistocene Human Footprints in French Caves. Issue 3 (6th May 2015) - Pastoors, Andreas; Lenssen-Erz, Tilman; Ciqae, Tsamkxao; Kxunta, Ui; Thao, Thui; Bégouën, Robert; Biesele, Megan; Clottes, Jean
Abstract : Some of the painted caves in southern France preserve human footprints from the Ice Age of 17, 000 years ago. Research has so far dealt with them sparsely and through a morphometric approach only. In 2013 three indigenous hunters/trackers from the Kalahari had an opportunity to read several spoor accumulations in four caves on the basis of their indigenous knowledge. As a result of this morpho-classificatory approach to track reading they produced new hypotheses on prehistoric cave visitors. Most spectacular is the narrative which the trackers generated from the footprints not far from the clay bison at Tuc d'Audoubert. Further research is planned to inspect more tracks and look into the epistemological status of the indigenous tracking method.